Tingkat Kesesuaian Gaya Kepemimpinan Ketua dengan Kematangan Anggota Hubungannya dengan Partisipasi Anggota - Abd. Rahman Pakaya (TRIKONOMIKA, 2013)
The purpose of this research is to know the leadership style’s compatibility level which including task behavior and relationship behaviors, the maturity of the members and the relationship with the with the participation of members of the Koperasi Unit Desa (KUD) in Gorontalo province. This study use 52 sample of KUD chairman and 140 sample members of KUD. The calculation of the sample used proportional sampling. Data were collected by interviews and distributing questionnaires to respondent. Method of anayisis using descriptive qualitative analysis techniques and quantitative methods. Hypothesis test using Kruskal Wallis different test and the Chi Quadrat. Based on the statistical analysis results can be concluded: (1) the existence of the leadership styles differentiation of the chairman, (2) there are differences in maturity level of members, (3) there is no leadership styles compatibility level of chairman toward the maturity of members in KUD at Gorontalo Province, and (4) there is a relationship of the chairman leadership style with the maturity of the members indicated from the participation of members.